Re-imagining the Pedagogical Paradigm Within a Technology Mediated Learning Environment - Brown Ken; Larionova Viola; Stepanova Natalia; Lally Vic (De Gruyter, 2019)
Traditional didactic pedagogies employed within the culture of the Russian higher education system precluded students' engagement with problems which were described as generating dissonances in learning cognition. Addressing issues of dissonance within the higher education learning sphere requires re-imagining the educational culture. Re-imagining provides an opportunity to promote new approaches to learning through alternative affordances; one such affordance is technology mediated learning.